EVALUATION OF GRAPE SEED EXTRACT (VITIS VINIFERA) AS A CROSSLINKER ON THE STABILITY OF DENTINE COLLAGEN IN TOTAL-ETCH ADHESIVE SYSTEMS: AN IN VITRO STUDY - D DENNIS,; FENIKA MAITARI, (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The bond strength between resin and dentine is determined by the integrity of collagen, dentine, and resin monomers. The susceptibility of the dentine bond results from the instability of the bonding structure that adheres to the bonding material. This can be achieved using collagen cross-linker, synthetically and naturally in dentine substrates which are effective in protecting collagen fibrils from degradation, as proanthrocyanidin. The aim of this study was to see the effect of grape seed extract as a crosslinker on the stability of dentine collagen and see the differences between groups. Methods: This study used 27 fresh premolars or third molars which were divided into three Groups, namely Group I giving grape seed extract 6.5%, Group II giving chlorhexidine 2%, and Group III only giving bonding ingredients. Samples were analyzed using scanning electron microscopy with ×1000 magnification. Results: Data were analyzed using kappa statistic, Kruskal–Wallis, and Mann–Whitney. The result of the study significant differences between treatment groups (p<0.05) and the 2% chlorhexidine group showed the highest value compared to the grape seed extract group and without treatment. Conclusion: Grape seed extract can be used as an alternative to chlorhexidine as a crosslinker to maintain bone strength of the composite restoration.